2023
DOI: 10.1371/journal.ppat.1011378
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of maternal cytomegalovirus-specific antibody responses and viral load to vertical transmission risk following primary maternal infection in a rhesus macaque model

Claire E. Otero,
Richard Barfield,
Elizabeth Scheef
et al.

Abstract: Cytomegalovirus (CMV) is the most common congenital infection and cause of birth defects worldwide. Primary CMV infection during pregnancy leads to a higher frequency of congenital CMV (cCMV) than maternal re-infection, suggesting that maternal immunity confers partial protection. However, poorly understood immune correlates of protection against placental transmission contributes to the current lack of an approved vaccine to prevent cCMV. In this study, we characterized the kinetics of maternal plasma rhesus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While the dosing and frequency of hyperimmune globulin also differed in these studies, a positive effect was only observed in women with very early infection, pointing to the potential importance of accuracy in the dating of infection recency. Recent studies have started to explore the role that antibody responses play in CMV transmission in a rhesus macaque model 61,62 . However, data in humans is limited and often confounded by the differing risk of infection associated with primary as compared to non-primary infection 63 .…”
Section: Discussionmentioning
confidence: 99%
“…While the dosing and frequency of hyperimmune globulin also differed in these studies, a positive effect was only observed in women with very early infection, pointing to the potential importance of accuracy in the dating of infection recency. Recent studies have started to explore the role that antibody responses play in CMV transmission in a rhesus macaque model 61,62 . However, data in humans is limited and often confounded by the differing risk of infection associated with primary as compared to non-primary infection 63 .…”
Section: Discussionmentioning
confidence: 99%